Amiloride is neuroprotective in the piglet neonatal hypoxic ischaemic encephalopathy model. (7th June 2011) - Chandrasekaran, M; Kato, T; Iwata, O; Bainbridge, A; Cady, E; Raivich, G; Robertson, N J
Abstract : Background: Blocking sodium protein transporters improves neuroprotection in vitro and in small animal models (Robertson1 ; Kendall2 ), In the current study we investigated the effects of treatment with the blood-brain permeable methyl isobutyl amiloride analogue (MIA) in the large animal model of neonatal hypoxic ischaemic encephalopathy. Methods: 18 male piglets (<24 h of age) underwent transient global hypoxia-ischaemia and were randomized to (1) normothermia or (2) 2.5 mg/kg of MIA at 10 min after resuscitation and 8 hourly thereafter. 1H MRS (Lac/Cr, Cho/Cr, NAA/Cr and Lac/NAA) in the thalamic and the dorsal subcortical white matter voxels. and 31P (Pi/ePP, PCr/ePP, NTP/ePP and pH) MRS were acquired serially up to 48 h after injury. Results: Post-insult treatment with MIA led to a significant decrease in thalamic Lac/NAA and Lac/Cr AUC (−45% and −24%, respectively, p<0.05, one-sided t-test). There was a reduction in TUNEL+ staining density in dorsoparietal and midtemporal cerebral cortex, thalamus and subcortical white matter. Piglets with progressive cerebral secondary energy failure (SEF) with NTP/ePP<40% of initial levels, showed massive intracerebral acidosis, with a trend towards reduced incidence in the MIA-treated group (p=0.05). Surprisingly, in animals without SEF, treatment with MIA did not cause a decrease in intracerebral pH. Conclusion: Treatment with MIA shows neuroprotection in post-ischaemic forebrain, and should be tested for synergistic effects in combination with cooling. The reduction in acidotic SEF and the absence of pH effects in animals without SEF suggest that the MIA neuroprotection is not exerted by reducing secondary intracellular alkalosis.